Evaluation of Physical Activity and its Association with Bio-Socio-Demographic Features among Female Adolescent Students of Selected Preparatory Schools in Kerbala City, Iraq - Rasoul, Sarah Sabah; Bdair, Ban Waheed Hussein; Almhanna, Moatasem Ghazi Hasoon; Abutiheen, Ali Abdulridha Kadhim (American Journal of Bioscience and Clinical Integrity, 2025)
Background: Promoting physical activity (PA) has become a major global public health priority. Moderate to vigorous PA is linked to improved immune and respiratory system function, lower body fat, lower cholesterol, and improved insulin sensitivity, which is linked to a lower chance of developing diabetes and cardiovascular diseases. This study aimed to evaluate of the association between PA and some bio-socio-demographic features among adolescent school girls in Kerbala City, Iraq. Methods: The study was a descriptive cross-sectional study on adolescent female students in the fourth and fifth grades aged 15 - 18 years, from 5 selected governmental preparatory schools in Kerbala city. Demographic characteristics, anthropometric measurements, PA, and recommended food scores (RFS) were assessed. Results: The results obtained showed that PA among adolescent school girls is strongly associated with maternal education and the family’s economic level. Also, the physically active subjects differed significantly from their inactive counterparts with respect to BMI categories (p = 0.005), BMI (p = 0.003), PA values (p < 0.0001), sleep time (p < 0.0001), screen time (p < 0.001) and RFS (p < 0.001). PA showed significant negative correlation with BMI (rs = -0.1923, p = 0.0290). Conversely, PA show significant positive correlation with sleep time (rs = 0.3022, p = 0.0005) and RFS (rs = 0.2451, p = 0.0051). Conclusion: The findings of this study suggest that PA among adolescent school girls is influenced significantly by maternal education and economic status of their families. Also, high BMI, poor sleep time, high screen time and poor diet quality reduces the tendency to engage in PA.